Deletion of Nrf2 enhances susceptibility to eosinophilic sinonasal inflammation in a murine model of rhinosinusitis. Issue 1 (3rd October 2018) - London, Nyall R.; Tharakan, Anuj; Mendiola, Michelle; Sussan, Thomas E.; Chen, Mengfei; Dobzanski, Alex; Lane, Andrew P.; Sidhaye, Venkataramana; Biswal, Shyam; Ramanathan, Murugappan
Abstract : Background: Oxidative stress exacerbates lower airway diseases including asthma and chronic obstructive pulmonary disease (COPD); however, its role in upper airway (sinonasal) chronic inflammatory disorders is less clear. Nuclear erythroid 2 p45‐related factor (Nrf2) is an endogenous mechanism that upon activation invokes an antioxidant response pathway via nuclear translocation and upregulation of cytoprotective genes. We sought to determine whether deletion of Nrf2 enhances susceptibility to allergic sinonasal inflammation in vivo. Methods: Nrf2 −/− mice were subjected to the ovalbumin (Ova)‐induced murine model of rhinosinusitis and indices of sinonasal inflammation and epithelial barrier dysfunction were assessed. Results: We show that deletion of Nrf2 results in enhances indices of allergen‐induced sinonasal inflammation including aggravated eosinophil accumulation and goblet cell hyperplasia. An exaggerated increase in epithelial derived inflammatory cytokines including interleukin 33 (IL‐33) and thymic stromal lymphopoietin (TSLP) was observed in the nasal lavage fluid and sinonasal mucosal tissue of Nrf2 −/− mice. Furthermore, Nrf2 −/− mice showed heightened Ova‐induced barrier dysfunction as measured by serum albumin accumulation in nasal lavage fluid of mice. Conclusion: These data show that the endogenous Nrf2 pathway limits Ova‐induced sinonasal inflammation, epithelial derived inflammatory cytokine production, and epithelial barrier dysfunction in vivo and identify a potential therapeutic target in the management of allergic sinonasal inflammatory disorders. This is the first study to our knowledge which shows that Nrf2 regulates allergic inflammation in the sinonasal cavity in vivo .